STRATEGIC METHODS EMPLOYED BY AMIR TEMUR TO ENSURE MORAL-PSYCHOLOGICAL STABILITY AND ENHANCE COMBAT READINESS IN HIS MILITARY FORCES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article analyzes the methods employed by Amir Temur to strengthen the moral and psychological condition of his troops and to maintain their fighting spirit at a high level, based on historical sources. The study provides a scholarly examination of the educational, religious–educational, disciplinary, and material incentive mechanisms applied during the Timurid period and their role in ensuring military power. In addition, Amir Temur’s spiritual and moral leadership strategy is evaluated from the perspective of modern military psychology.